MAKNA UPACARA TEPUK TEPUNG TAWAR PADA PERNIKAHAN ADAT MELAYU RIAU Di Desa Pematang Sikek Kecamatan Rimba Melintang Kabupaten Rokan Hilir Provinsi Riau - Suwira Putra; Efni Noor Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The ceremony tepuk tepung tawar is a cultural activity and practice Malay culture. This ceremony is also a tradition / habit inherited family passed down from generation to generation is performed at the wedding. Ceremony is also believed to have meaning as a gift and blessing prayer for the welfare of both the bride and her entire family, as it also significantly as a symbol of rejection against any reinforcements and the possible receipt of future disturbances. This study aims to determine the meaning of the symbols and symbolics and values contained and benefit what is obtained from the ceremony in traditional wedding Malay Riau.This study applies qualitative methods of data collection were obtained based on the fact that in location occurs through observation, interviews, and documentation. Informants were selected by purposive sampling technique, where informen in this study of 10 people, consisting of (traditional leaders, actors ceremony Tepuk Tepung Tawar). The study uses the theory of Symbolic Interaction. Data analysis techniques to reduce the data, collecting data, presenting the data, draw conclusions and evaluation using data validity checking technique that is an extension of participation and triangulationThe research shows that this ceremony is not only regarded as having meaning giving ceremony of prayer and blessing for the well-being of both the bride and her entire family and as a mere gathering of media alone. In addition, this ceremony has a broad meaning ranging from tools and materials, Tepuk Tepung Tawar actors, procedures do. As for the value contained in this ceremony is a social values, family values, religious and cultural values. Coupled also with benefit obtained from perpetrators and implementers ceremony between Tepuk tepung Tawar is delivered prayers, hopes, goals and expectations, friendship, prayed for the good and preservation of culture.Key word: ceremony, tepuk tepung tawar, mean, value, benefit.